The osteocyte and its osteoclastogenic potential - Marahleh, Aseel; Kitaura, Hideki; Ohori, Fumitoshi; Noguchi, Takahiro; Mizoguchi, Itaru (Frontiers in Endocrinology, 2023)
The skeleton is an organ of dual functionality; on the one hand, it provides protection and structural competence. On the other hand, it participates extensively in coordinating homeostasis globally, given that it is a mineral and hormonal reservoir. Bone is the only tissue in the body which goes through strategically consistent bouts of bone resorption to ensure its integrity and organismal survival in a temporally and spatially coordinated process, bone remodeling. Bone remodeling is directly enacted by three skeletal cell types, osteoclasts, osteoblasts, and osteocytes; these cells represent the acting force in a basic multicellular unit and ensure bone health maintenance. The osteocyte is an excellent mechanosensory cell and has been positioned as the choreographer of bone remodeling. It is, therefore, not surprising that a holistic grasp of the osteocyte entity in bone is warranted. This review discusses osteocytogenesis and associated molecular and morphological changes and describes the osteocytic lacunocanalicular network (LCN) and its organization. We highlight new knowledge obtained from transcriptomic analyses of osteocytes and discuss the regulatory role of osteocytes in promoting osteoclastogenesis with an emphasis on the case of osteoclastogenesis in anosteocytic bones. We arrive at the conclusion that osteocytes exhibit several redundant means through which osteoclast formation can be initiated. However, whether osteocytes are true "orchestrators of bone remodeling" cannot be verified from the animal models used to study osteocyte biology in vivo. Results from studying osteocyte biology using current animal models should come with the caveat that these models are not osteocyte-specific, and conclusions from these studies should be interpreted cautiously.